Toaff's way - Voigt, Cynthia; Hanson, Sydney (New York : Alfred A. Knopf, 2018)
"Toaff is a small squirrel full of big questions. Why must I stay away from the human's house? Why shouldn't I go beyond the pine trees? Why do we fight with the red squirrels across the drive? His sister shrugs--that's just the way things are. His brother bullies--because I said so. And the older squirrels scold--too many questions! Can Toaff really be the only one to wonder why?"--Amazon.com.
Keywords: Farm life -- Juvenile fiction; Squirrels -- Juvenile fiction; Farm life -- Fiction; Squirrels -- Fiction; JUVENILE FICTION -- Action & Adventure; JUVENILE FICTION -- Animals -- Squirrels; JUVENILE FICTION -- Legends, Myths, Fables -- Farm & Ranch Life; Squirrels -- Juvenile fiction; Juvenile works; Action and adventure fiction